2004
DOI: 10.1158/0008-5472.can-03-1307
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Gene Transfer of the Human Inducible Nitric Oxide Synthase Gene Enhances the Radiation Response of Human Colorectal Cancer Associated with Alterations in Tumor Vascularity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 37 publications
2
42
1
Order By: Relevance
“…2 The combination of gene therapy and radiation has also demonstrated synergistic antitumor effects both in vitro and in vivo in several tumor models. 6,13 The combination of an oncolytic adenoviral vector with Taxol produces an additive antitumor effect in preclinical studies in mouse xenograft tumor models. 4 Thus, combination treatment has great potential for translation into effective clinic therapy in the immediate future.…”
Section: Discussionmentioning
confidence: 99%
“…2 The combination of gene therapy and radiation has also demonstrated synergistic antitumor effects both in vitro and in vivo in several tumor models. 6,13 The combination of an oncolytic adenoviral vector with Taxol produces an additive antitumor effect in preclinical studies in mouse xenograft tumor models. 4 Thus, combination treatment has great potential for translation into effective clinic therapy in the immediate future.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of cancer therapy using NO, including inducible NO synthase gene therapy and administration of NO donor, was recently confirmed in animal models (45)(46)(47). Consequently, NO therapy has received considerable attention and is currently undergoing clinical evaluation for cancer prevention (48).…”
Section: Discussionmentioning
confidence: 99%
“…Specific MEK1/2 inhibitors can inhibit the expression of phospho-ERK1/2 for various lengths of time in vitro (36)(37)(38). CI-1040, a MEK1/2 inhibitor, reduced tumor growth by 31.3% in mice inoculated with papillary thyroid carcinoma (PTC) cells carrying a BRAF mutation and by 47.5% in mice inoculated with PTC cells bearing a RET/ PTC1 rearrangement (39). Cl-1040 has been tested in other cancers, including colon cancer, breast cancer, non-small cell lung cancer (NSCLC), and melanoma, and was well tolerated by patients in phase I-II trials (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…(27). It has been reported that the adenoviral gene transfer of the iNOS gene enhances the radiation response of human colorectal cancer associated with alterations in tumor vascularity (28).…”
Section: Discussionmentioning
confidence: 99%